MoS2 Nanosheet–Pd Nanoparticle Composite for Highly Sensitive Room Temperature Detection of Hydrogen. Issue 4 (2nd March 2015) - Kuru, Cihan; Choi, Chulmin; Kargar, Alireza; Choi, Duyoung; Kim, Young Jin; Liu, Chin Hung; Yavuz, Serdar; Jin, Sungho
Abstract : Highly sensitive hydrogen detection at room temperature can be realized by employing solution‐processed MoS2 nanosheet–Pd nanoparticle composite. A MoS2 –Pd composite exhibits greater sensing performance than its graphene counterpart, indicating that solvent exfoliated MoS2 holds great promise for inexpensive and scalable fabrication of highly sensitive chemical sensors.